PENGGUNAAN TEPUNG GEMBOLO (Dioscorea bulbifera L.) SEBAGAI BAHAN PENSUBSTITUSI TERIGU PADA PEMBUATAN MIE KERING - Herlina Herlina; Sih Yuwanti; Intan Nurlaili (Faculty of Agricultural Technology, University of Jember, 2015)
Gembolo is plant tubers that potentially applied in food as the tubers has a high content of glucomannan which can improve the texture of food products. Gembolo flour can be used as substitution for wheat flour in the manufacture of dried noodles. Blanching improved the brightness of gembolo flour. This study aimed to determine the substitution and blanching treatment which produced dried noodles with the best physical, chemical, and organoleptic characteristics. Parameters that analyzed in this research were color, rehydration, expand ability, cooking loss, elasticity, moisture content, ash content, fat content, protein content, carbohydrate content, and organoleptics. The best treatment based on effectivity test was A1B1 (10% substitution concentration of gembolo without blanching flour) with the following characteristics: L (Lightness) 55,40, rehydration 140,47%, expand ability 127,64%, elasticity 25%, cooking loss 6, 00%, moisture content 9,53%, ash content 1,50%, fat content 1,54%, protein content 14,46%, carbohydrate content 73,24%, scores for preference color 3,16, texture 3,16, taste 3,64 and overall preference 3,20.Keywords: gembolo flour, substituent, dried noodle